Cost-Benefit Analysis in Planning Processes: An Interactive Instrument in an Integrated Approach - Stijn Reinhard; Aris Gaaff (European Regional Science Association (ERSA), 2006)
Increasing pressure on space demands careful assessment between competing functions in a planning process. Especially, in metropolitan landscapes, space is in short supply and hence expensive. Housing, industrial sites and office parks, and infrastructure are strong drivers of landscape change, often dominating nature and landscape which represent values with a more collective good character. Nevertheless, in The Netherlands, nature is becoming an important force in spatial planning. This assessment between competing functions, requires interactive planning and appropriate instruments. In the usual planning process, the costs and benefits of the development plans to society are only computed in the final stage of the process. We argue in this paper for integration of a social cost-benefit analysis (SCBA) in interactive regional planning processes. Firstly, it avoids time and money being spent on elaborating a plan, which is not beneficial to society. Secondly, it helps to prevent unwarranted enthusiasm for inauspicious plans among participants. From earlier studies, we learned that in the application of SCBA the discussion between researchers, clients and other participants should focus on two or three clearly distinctive models. Too much detail should be avoided. On the other hand, key indicators used in calculating effects have to be available and well documented. The summation of the costs and benefits provides a first impression of the financial and social feasibility of the plan. In a first planning session, therefore, a common understanding of the mechanisms underlying the assessment of the plan will be built up. This improves the support for SCBA of the final project. It also provides the stakeholders and shareholders with information about the feasibility of the plan at an early stage. Another advantage is that SCBA focuses on the benefits to society as a whole. Recently, we have spent much effort in the development of an interactive tool that is both relevant and user friendly. Relevant means that it takes into account the essential values of different types of land use and their interaction. At the moment we focus on spatial interaction and incorporating ecological network values. A prototype of the interactive integrated model is available for demonstration.
Keywords: 330